Defect formation in CsI-CsBr mixed crystals - Garapyn, I.V.; Hud, I.Z.; Pavlyk, B.V. (Functional Materials, 2005)
The defect structure of Csl-CsBr mixed crystals has been studied by electroconductivity and thermostimulated depolarization current (TSDC) methods. The formation of Csl₀.₉₃Br₀.₀₇ solid solution is found to be accompanied by increase of conductivity as compared to that of pure Csl. The physical processes causing the appearаnce of TSDC maxima at 300 К and 385 К have been considered. The results obtained evidence the
increase of anion vacancy concentration and unchanged concentration of cation vacancies in Csl₀.₉₃Br₀.₀₇ mixed crystals. Дослiджено дефектну структуру змiшаних кристалiв Csl-CsBr методами електропровiдностi та струмiв термостимульованої деполяризацiї (ТСД). Встановлено, що утворення твердого розчину Csl₀.₉₃Br₀.₀₇ супроводжується збiльшенням провiдностi порiвняно з провiднiстю чистого Csl. Проаналiзовано фiзичнi процеси, що спричиняють появу максимумiв ТСД при температурах 300 К та 385 К. Одержанi результати свiдчать про пiдвищення концентрацiї анiонних та незмiнну концентрацiю катiонних вакансiй в змiшаних кристалах Csl₀.₉₃Br₀.₀₇. Дефектная структура смешанных кристаллов Csl-CsBr исследована методами электропроводности и токов термостимулированной деполяризации (ТСД). -Установлено, что возникновение твёрдого раствора Csl₀.₉₃Br₀.₀₇ сопровождается увеличением проводимости по сравнению с проводимостью чистого Csl. Проанализированы физические процессы, обусловливающие возникновение максимумов ТСД при температурах 300 К и 385 К. Полученные результаты свидетельствуют о повышении концентрации анионных и неизменной концентрации катионных вакансий в смешанных кристаллах Csl₀.₉₃Br₀.₀₇.